First three-dimensional skull of the Middle Triassic mixosaurid ichthyosaur Phalarodon fraasi from Svalbard, Norway - Roberts, Aubrey Jane; Engelschiøn, Victoria Sjøholt; Hurum, Jørn Harald (Zenodo, 2022)
Roberts, Aubrey Jane, Engelschiøn, Victoria Sjøholt, Hurum, Jørn Harald (2022): First three-dimensional skull of the Middle Triassic mixosaurid ichthyosaur Phalarodon fraasi from Svalbard, Norway. Acta Palaeontologica Polonica 67 (1): 51-62, DOI:10.4202/app.00915.2021, URL: http://dx.doi.org/10.4202/app.00915.2021